Βook Review: E. C. Bourbouhakis (έκδ.), Not Composed in a Chance Manner: The Epitaphios for Manuel I Komnenos by Eustathios of Thessalonike [Acta Universitatis Upsaliensis, Studia Byzantina Upsaliensia 18], Uppsala 2017, - ΜΕΡΙΑΝΟΣ Γεράσιμος (Byzantina Symmeikta, 2020)
Βook Review: E. C. Bourbouhakis (έκδ.), Not Composed in a Chance Manner: The Epitaphios for Manuel I Komnenos by Eustathios of Thessalonike [Acta Universitatis Upsaliensis, Studia Byzantina Upsaliensia 18], Uppsala 2017,